An innovative method of upgrading old rail tunnels under continued operation – Example Rekawinkler‐ and Kleiner Dürreberg Tunnel: Innovative Methode zur Ertüchtigung alter Eisenbahntunnel unter Betrieb – Beispiel Rekawinkler‐ und Kleiner Dürrebergtunnel. Issue 5 (2nd October 2017) - Seywald, Christian; Helmberger, Albert; Matt, Robert
Abstract: The ÖBB‐Infrastruktur AG operates and maintains 246 tunnels and similar structures with an overall length of approx. 250 km. Nearly 150 of these structures are more than 100 years old, 35 of them are over 150 years old. Ageing processes, the impact of train traffic, ground conditions and environmental conditions are causing progressive damage to the tunnel linings, which – in order to maintain safe railway operation – requires ongoing maintenance procedures. Those procedures are carried out under a range of restrictions concerning availability, which is one of the most important principles at the ÖBB after safety. In order to obtain continuous availability of the facility, new methods of refurbishment were developed for the two double‐track tunnels Rekawinkler Tunnel and Kleine Dürreberg. The described methods enabled extensive repair works of the tunnels, mostly with uninterrupted train traffic on the second track.